Causes and predictors of 30‐day readmission in patients with syncope/collapse: a nationwide cohort study - Kadri, Amer N. (2018)
Background Syncope accounts for 0.6% to 1.5% of hospitalizations in the United States. We sought to determine the causes and predictors of 30‐day readmission in patients with syncope. Methods and Results We identified 323 250 encounters with a primary diagnosis of syncope/collapse in the 2013-2014 Nationwide Readmissions Database. We excluded patients younger than 18 years, those discharged in December, those who died during hospitalization, hospital transfers, and those whose length of stay was missing. We used multivariable logistic regression analysis to evaluate the association between baseline characteristics and 30‐day readmission. A total of 282 311 syncope admissions were included. The median age was 72 years (interquartile range, 58-83), 53.9% were women, and 9.3% had 30‐day readmission. The most common cause of 30‐day readmissions was syncope/collapse, followed by cardiac, neurological, and infectious causes. Characteristics associated with 30‐day readmissions were age 65 years and older (odds ratio [OR], 0.7; 95% confidence interval [CI], 0.6-0.7), female sex (OR, 0.9; 95% CI, 0.8-0.9), congestive heart failure (OR, 1.5; 95% CI, 1.2-1.9), atrial fibrillation/flutter (OR, 1.3; 95% CI, 1.3-1.4), diabetes mellitus (OR, 1.2; 95% CI, 1.2-1.3), coronary artery disease (OR, 1.2; 95% CI, 1.2-1.3), anemia (OR, 1.4; 95% CI, 1.4-1.5), chronic obstructive pulmonary disease (OR, 1.4; 95% CI, 1.3-1.4), home with home healthcare disposition (OR, 1.5; 95% CI, 1.5-1.6), leaving against medical advice (OR, 1.7; 95% CI, 1.6-1.9), length of stay of 3 to 5 days (OR, 1.5; 95% CI, 1.4-1.6) or >5 days (OR, 2; 95% CI, 1.8-2), and having private insurance (OR, 0.6; 95% CI, 0.6-0.7). Conclusions The 30‐day readmission rate after syncope/collapse was 9.3%. We identified causes and risk factors associated with readmission. Future prospective studies are needed to derive risk‐stratification models to reduce the high burden of readmissions.